A conservação da biodiversidade segundo alunos do curso de ciências biológicas - Söncksen, Beatriz Malaghine (2017)
The educational process that involves environmental issues is fundamental to every Brazilian citizen. The university's role is to reflect on the problems of the community, to guide its students in finding solutions to the difficulties encountered and to implement an education that is truly environment-oriented. Effective protection of the environment requires the involvement and commitment of the public to ensure the maintenance of natural resources for this and future generations. In this way, in particular the students of the biological sciences courses, have a great importance and responsibility in transmitting correct and real information to the society. The main objectives of this study were: i) to evaluate what and how the students of the biology course (baccalaureate and licenciatura) understand and value the conservation of nature; Ii) what situations / species / actions students choose as priorities for conservation, and what factors influence their choices. A total of 122 undergraduate students in Biological Sciences (undergraduate and baccalaureate) from the University of Sacred Heart and the Regional Education Foundation of Avaré were interviewed using a semi-structured questionnaire with questions focused on conservation in general. It was verified that undergraduate students of the Biological Sciences course have a clear vision on the issues of nature conservation, report the theme as of great importance, both in school curricula and the insertion of the theme in society, and use the most Such as restoration of habitats, environmental education and creation of parks for a more effective nature conservation, but there is still a need to incorporate disciplines directly related to nature conservation, altering the curricular bases of university courses, increasing and guaranteeing The conservationist vision in the university in general. So that the country can train professionals with a broad vision of the environmental problem and the capacity to make socio - economic - environmental decisions